THE RATIONAL APPROACH TO THE PROVED THERAPY OF АТОPIC DERMATITIS - КaliuzhnaL.D.; ShmigloM.М.; IbragimU.Т.; UvarenkoЕ.А. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Atopic dermatitis represents as the multifactor generically determined disease of a skin. They determined a general level IgE and allergen specific IgE-antibody to an acaruses of a home dust, investigated association of atopic dermatitis with fungal infection of a skin and its appendages, determined a status of lipid peroxidation in the patients with atopic dermatitis.